Manifestation of Virtuous Life in Each of the Six Dimensions of Elementary Educational Content - Sabah Abdi; Rashid Ahmadifar (پژوهش در آموزش معارف و تربیت اسلامی)
The aim of this study was to examine the manifestation of a virtuous life (Hayat Tayyibah) in each of the six dimensions of elementary educational content. This research employed content analysis using the three-stage Shannon entropy method. The statistical population included the content of the social studies curriculum for elementary education in Iran for the academic year 1402-1403, encompassing four textbooks, all of which were selected as the sample through census sampling. The research instrument was a checklist designed based on the opinions of 13 experts in each of the six educational dimensions. The reliability was confirmed using Holsti's method (0.89), and the validity was ensured through expert opinions and prolonged engagement with the research. The results showed that among the 1069 instances related to Hayat Tayyibah, the political and social dimension had the highest frequency with 378 instances (35%), while the artistic and aesthetic dimension had the lowest frequency with 60 instances (6%). Shannon entropy analysis further confirmed that there is no balance or proportion among the subcomponents of Hayat Tayyibah within each of the six dimensions. Additionally, although the frequency of Hayat Tayyibah components in social studies textbooks is nearly equal, their importance coefficients vary. The concept of Hayat Tayyibah in both worldly and hereafter life in Islamic culture is so significant that all aspects of life should be organized based on it. Therefore, the content of elementary textbooks in this domain requires serious review and revision. However, these instances are not equally and uniformly distributed across the six educational dimensions.